2016
DOI: 10.1021/acs.jpcc.6b05794
|View full text |Cite
|
Sign up to set email alerts
|

How Should Iron and Titanium be Combined in Oxides to Improve Photoelectrochemical Properties?

Abstract: We discuss here for the first time how to combine iron and titanium metal ions to achieve a high photo-electrochemical activity for TiO 2 -based photo-anodes in water splitting devices. To do so, a wide range of photoelectrode materials with tailored Ti/Fe ratio and element vicinity were synthesized by using the versatility of aqueous sol-gel chemistry in combination with a microwave-assisted crystallization process. At low ferric concentrations, single phase TiO 2 anatase doped with various Fe amounts were pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
2
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 91 publications
3
27
2
2
Order By: Relevance
“…The determined unit cell parameters and atomic positions are given in table 1. Refinement of ion occupancy showed that differing from the previously obtained fully disordered structure [19] iron ions showed a slight preference for 4c sites occupying royalsocietypublishing.org/journal/rsos R. Soc. Open Sci.…”
Section: Photocatalytic Experimentscontrasting
confidence: 65%
“…The determined unit cell parameters and atomic positions are given in table 1. Refinement of ion occupancy showed that differing from the previously obtained fully disordered structure [19] iron ions showed a slight preference for 4c sites occupying royalsocietypublishing.org/journal/rsos R. Soc. Open Sci.…”
Section: Photocatalytic Experimentscontrasting
confidence: 65%
“…The conventional cell of Fe 2 TiO 5 (orthorhombic structure, space group #63), which contains 32 atoms, was relaxed using the Monkhorst-Pack scheme 21 with a 9 × 3 × 3 k-points grid until the force on each atom was less than 0.005 eV Å −1 . Because the exact state of the FeIJIII) atoms is not clear, 6 we performed all calculations with the most stable spin state: antiferromagnetic configuration. The calculated band gaps with conventional DFT are underestimated compared to the experimental ones.…”
Section: Computational Detailsmentioning
confidence: 99%
“…In comparison with α-Fe 2 O 3 and anatase TiO 2 , Fe 2 TiO 5 exhibits intermediate behavior with desirable optical band gap compared to α-Fe 2 O 3 and electronic transport compared to anatase TiO 2 . 6 Among various investigated materials, Fe 2 TiO 5 is expected to be an excellent substitute for TiO 2 in many potential applications, including water oxidation, 1 photo-degradation, 2 ceramic pigments, 3 proton exchange membranes, 4,7 Li-ion battery anodes 8,9 and gas sensors. 10 It consists of earth-abundant elements (obtainable from ilmenite mineral), 11 exhibits high chemical surface stability, and a relatively small band gap (2.1 eV).…”
Section: Introductionmentioning
confidence: 99%
“…Por fim, para que seja possível a transferência dos portadores de carga para as espécies reacionais faz-se necessário que as bandas de valência (VB) e de condução (CB) do material apresentem posicionamentos compatíveis com os potenciais de oxi-redução das reações de interesse. A eficiência da etapa de transferência dos portadores, entretanto, não é determinada apenas pelas propriedades da estrutura do material, mas também pela estrutura eletrônica da interface com o meio [6].…”
Section: Mecanismos De Fotoativaçãounclassified
“…Apesar das excelentes propriedades particularmente interessantes para o seu uso para fotocatálise, o TiO 2 ainda mantém duas grandes limitações que comprometem a sua aplicação: (1) elevada energia de band-gap; e (2) alta taxa de recombinação dos portadores de carga [6]. Nesse sentido, diferentes estratégias têm sido adotatadas para aprimorar a eficiência de fotoabsorção do material mantendo sua boa combinação de propriedades catalíticas.…”
Section: Dióxido De Titâniounclassified